Chemobiological synthesis of benzene, toluene, ethylbenzene, and xylene from glucose or glycerol - Xuan Zou; Taewan Kim; Zi Wei Luo; Kyeong Rok Choi; Sunkyu Han; Sang Yup Lee (Proceedings of the National Academy of Sciences, 2025)
Benzene, toluene, ethylbenzene, and p -xylene (BTEX) are key aromatic hydrocarbons widely used in fuels, polymers, and industrial chemicals, yet their production remains heavily dependent on fossil resources, raising environmental and public health concerns. To promote de novo production of BTEX from renewable feedstocks, we developed a chemobiological platform that integrates microbial biosynthesis with chemical deoxygenation. Four metabolically engineered Escherichia coli strains were constructed to produce one of four oxygenated precursors of BTEX—phenol, benzyl alcohol, 2-phenylethanol, or 2,5-xylenol—from glucose or glycerol. After in situ two-phase extractive fermentation of the individual engineered strains using isopropyl myristate (IPM) as the organic solvent, the organic phase containing one of the oxygenated precursors was separated from the aqueous phase and subjected to distinct chemical deoxygenation reactions to reduce the precursor to the corresponding BTEX compound. This modular approach, based on the compatible organic solvent, streamlines biotransformation and consecutive chemical derivatization, providing a practical and viable route to sustainable BTEX production. The platform is extensible and provides a generalizable framework for integrating biosynthesis with chemical deoxygenation in hybrid bioprocessing.